Um instrumento para avaliação da aderência de ferramentas de gerenciamento de projetos ao guia PMBOK - (:unkn) unknown (Universidade Federal do Pampa, 2014)
The adoption of good project management tools that are adherent to established standards of management as the PMBOK is increasingly necessary, due to support decision making provided by these tools, and the historical failure of technology projects information. This work presents an evaluation instrument for project management tools. This instrument allows the verification of desirable quality requirements in these tools, and mainly, it allows evaluating the tool adherence degree to the PMBOK processes, which is a globally recognized guide that meets a range of project management knowledge. This evaluation instrument is based on the NBR ISO/IEC 9126-1 norm that describes a software product quality model, grounded on quality characteristics and subcharacteristics. Those quality characteristics were transformed into evaluation goals, and for each goal questions related to the PMBOK processes and desirable requirements management tools were elaborated. Measures were taken from a set of questions to evaluate the PMBOK processes adherence degree of the tools. In order to check the instrument effectiveness, was using an adapted evaluation process of ISO/IEC 14598-1 to apply the instrument in six different tools. Through the evaluation it was possible to identify the adherence of each tool to the PMBOK processes, and to verify which PMBOK knowledge area are the more assisted and which receive less support. Additionally, the analysis of the results allowed the viability verification of the evaluation instrument, both in a coverage review, and depth. Are expected that this work will contribute to the project managers have a better backrest in the project administration tool selection that best assist their needs and expectations.
Keywords: Software Engineering; Information Technology; Project Management; Evaluation; PMBOK Guide; Tools; Engenharia de software; Tecnologia da informação; Gerenciamento de Projetos; Avaliação; Guia do conjunto de conhecimentos em gerenciamento de projetos (Guia PMBOK); Ferramentas; CNPQ::CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO